Kartu Rumpang Bergambar sebagai salah satu media Pembelajaran Arab-Melayu di Sekolah Dasar - Muhammad Ridlo Alfianto; Muhamad Agil Wildan; Yudha Putra Permana; Aly Muhammad Gany; Amelia Audina; Budiana Budiana (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2019)
PKM-M was done at SDN 011 Bengkong Batam using Rumpang Bergambar. The Arabic-Malay learning method was used by 10 types of cards which are divided into 2 main groups. The first group got 1-6 card with 3 rumpang while the second group got 7-10 card with 2 rumpang. The learning process was carried out by using mentoring techniques and group sharing. Each group divided will be accompanied by a designated companion before the learning process begins. Based on the results of PKM-M activities, the maximum number of cards that can be completed by all of the group is 4 cards, there are several groups who are unable to write Arabic-Malay completely and correctly in 3 and 2 Rumpang. Further recommendation for Arabic-Malay learning is to make Rumpang Bergambar Termodifikasi Methode with Connecting sentence Technique